TROMBOSIT ABNORMAL PASCAPERSALINAN - Prihatini .; S. Hadi; Wijanda H T Sylvaranto; Maksum . (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2009)
Pregnant women with cardio vascular failure caused by hypertension may show pre-eclampsia or eclampsia syndrome. The syndromewas confirmed by the hypertension family history when she was pregnant or during labour formerly. The influence was shown in thehaematological examination, besides inducing hypertension during pregnancy. The examination must be an accurate laboratory procedureto avoid complication. The routine obstetric examination should be a physical, laboratory as well as USG one. Exspecially laboratoryexamination for pre-eclampsic and eclampsic patients like clinical chemistry, blood examination, urinalysis and special examinationas ANA, ACA and TAT The result of laboratoric examination showed anemic,trombosits was normal and TAT abnormal. The baby wasborn normal. After 3 months post labour the result of TAT still hyper-reactive especially for ADP agonist and hypo-reactive for collagenagonist. This patient have a trombosit function failure based on TAT and must be care to cardiovascular disease. Pregnant women withpre-eclamptic or eclamptic risk must be monitored the trombosit function beside clinical laboratoric and obstetric examinations